Low-dose phloretin alleviates diabetic atherosclerosis through endothelial KLF2 restoration. Issue 4 (2nd April 2020) - Xia, Yong; Feng, Hua; Li, Zhen-Wei; Tang, Kuan-Xiao; Gao, Hai-Qing; Wang, Wei-Ling; Cui, Xiao-Pei; Li, Xiao-Li
ABSTRACT: We investigated whether low-dose phloretin served as daily dietary supplements could ameliorate diabetic atherosclerosis and the role of kruppel‐like factor 2 (KLF2). HUVECs cultured in high glucose medium were treated with different concentrations of phloretin and KLF2 mRNA, and protein level was detected. Diabetes was induced using streptozotocin in Apoe −/- mice after which they were fed a high-cholesterol diet for 8 weeks. Diabetic mice injected with KLF2 shRNA-lentivirus or control virus were treated with 20 mg/kg phloretin. Glucose, lipid profile, aortic atheroma, and endothelial nitric oxide synthase (eNOS) expression were detected. Phloretin retained endothelial function by KLF2-eNOS activation under hyperglycemia. Low-dose phloretin helped with lipid metabolism, and blocked the acceleration of atherosclerosis in STZ-induced diabetic mice since the early stage, which was diminished by KLF2 knockdown. Low-dose phloretin exhibited athero-protective effect in diabetic Apoe −/- mice dependent on KLF2 activation. This finding makes phloretin for diabetic atherosclerosis. Graphical abstract: : Oil red O-stained sections of atherosclerotic lesion area in the aortic root